2018
DOI: 10.3389/fncel.2018.00170
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Programed Cell Death-1 and CD4+ T Cell Alterations in Different Phases of Ischemic Stroke Patients

Abstract: Objective: We aimed to analyze alterations in T cell subgroups during different post-ischemic stroke (IS) phases to explore the possible mechanisms underlying stroke-induced immune depression (SIID).Methods: Sixty-four IS patients who met the entry criteria were divided into three groups: an acute phase group, a sub-acute phase group and a stable phase group. Fourteen healthy individuals were selected as normal controls. The phenotype distribution of T cells in patient peripheral blood was analyzed, and the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, IL-15 was also reported to defend astrocytes against oxygen-glucose deprivation (OGD)-induced damage and death, and astrocytes could protect neurons from ischaemic injury and sustain BBB integrity [129], which are contradictory Bodhankar et al identified that PD-1 and CTLA-4 had inhibitory effects on the activation of T cells in a rodent stroke model [151] and that blockade of the PD-L1 checkpoint significantly limited the CNS inflammatory response and improved neurological outcomes by partially reversing splenic atrophy and increasing the accumulation of CD8 + Treg cells in the lesioned brain hemisphere [131]. This suggests the application potential of a novel therapy using accessible humanized anti-PD-L1 antibodies to treat human stroke subjects and confirms that PD-1 is inversely correlated with the absolute amount of CD4 + T central memory (TCM) cells in ischaemic patients [135]. However, these conclusions remain to be validated in clinical trials.…”
Section: Cytokines Small Molecules Neutralizing Antibodies and Cell Epitopes As Targetsmentioning
confidence: 63%
“…However, IL-15 was also reported to defend astrocytes against oxygen-glucose deprivation (OGD)-induced damage and death, and astrocytes could protect neurons from ischaemic injury and sustain BBB integrity [129], which are contradictory Bodhankar et al identified that PD-1 and CTLA-4 had inhibitory effects on the activation of T cells in a rodent stroke model [151] and that blockade of the PD-L1 checkpoint significantly limited the CNS inflammatory response and improved neurological outcomes by partially reversing splenic atrophy and increasing the accumulation of CD8 + Treg cells in the lesioned brain hemisphere [131]. This suggests the application potential of a novel therapy using accessible humanized anti-PD-L1 antibodies to treat human stroke subjects and confirms that PD-1 is inversely correlated with the absolute amount of CD4 + T central memory (TCM) cells in ischaemic patients [135]. However, these conclusions remain to be validated in clinical trials.…”
Section: Cytokines Small Molecules Neutralizing Antibodies and Cell Epitopes As Targetsmentioning
confidence: 63%
“…Thus, it could affect the Tim-3 positive T lymphocyte proliferation [29], function [46] and secretion of cytokines [31]. Our previous study indicated that there was elevation of Tim-3 on the peripheral blood T lymphocytes in the stroke [32]. We speculated that CEACAM1 could bind with Tim-3 through the T lymphocyte surface, which may induce injury of immune function of lymphocytes at the late stage IS patients, and nally result in increased risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is closely related to the proliferation and apoptosis of neutrophils and lymphocytes [27][28][29], together with the secretion of cytokines [30,31]. Our previous study indicated that there was signi cant elevation of CD8 + T cell TIM-3 in the stroke patients [32], and CEACAM1 was also one of the ligands for TIM-3 [33]. NGAL is reported to be involved in the innate immunity, cellular differentiation and proliferation, as well as iron homeostasis [34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented increased CD69 + T cells in the palatine tonsils and cervical lymph nodes of stroke patients 76 h following stroke onset [80], and that activated T cells reactive to myelin oligodendrocyte glycoprotein accumulate in the brain following experimental stroke, implicating activated T cells in driving autoimmunity post-stroke [81,82]. Conversely, an exhausted T cell phenotype characterized by an increased frequency of PD-1 + CD4 + T cells has also been observed in patients 48 h post-stroke [83]. Given the diverse T cell phenotypes and their pleiotropic roles post-stroke, it becomes crucial to dissect mechanisms that control immunoregulatory programmes in T cells balancing the requirement for a tightly regulated anti-microbial immune response versus initiating an autoimmune reaction.…”
Section: Discussionmentioning
confidence: 99%